Isolation and Characterization of Shrimp Shell Chitosan - Tankoiko, Soghi; Alam, Yanuar Bakhrul; Matlubah, Uno Sheva; Hidayati, Irul; Andiarna, Funsu; Agustina, Eva (International Conference on Sustainable Health Promotion, 2023)
Chitosan is a polysaccharide formed through the deacetylation of chitin. Chitosan is commonly produced from the waste of the fishing industry, such as shrimp, crab, or lobster shells with a process that first extracts the chitin and then goes to deacetylation. This research aims to isolate and characterize chitosan derived from shrimp to examine its physicochemical properties using various methods. The moisture content was determined by drying the sample in an oven (13.1%), indicating a relatively high moisture level compared to the Indonesian National Standard (SNI) scale (12%), while the ash content was obtained through combustion (8.68%). FTIR analysis identified characteristic peaks at 3500-3000 cm^-1 (OH group), 1600-1500 cm^-1 (amide C=O group), ±1600 cm^-1 (N-H group), and ±1000 cm^-1 (C-N group), which are typical features of chitosan’s structure. The degree of deacetylation, indicating a reduction in acetylation groups, was calculated through acid-base titration (20.196%), confirming the formation of chitosan. The result of the deacetylation degree is way below the SNI standard (>75%). Information about these chitosan characteristics highlights its potential applications in the food, pharmaceutical, and agricultural industries.